Qualification of Hairpin Motors Insulation for Automotive Applications - Mancinelli, Paolo; Stagnitta, Simone; Cavallini, Andrea (IEEE transactions on industry applications, 2017)
This paper is focused on the reliability evaluation of an electric vehicle (EV) motor based on hairpin technology. Besides bearings (not discussed here), the weak point of an electric motor is its insulating system. For inverter-fed motors, the inception of partial discharges might lead to failure in a matter of days, and thus, deserves particular attention. Qualification and lifetime evaluation of inverter-fed machines are described in IEC 60034-18-41, which specifies accelerated aging procedures and considers partial discharge inception as the end-of-life criterion. This standard was used as a reference for this paper. The only exception is that insulation models were subjected to the mechanical stress profile reported in the ISO 16750-3-2012 standard since an automotive motor is subject to significant vibrations during its operation. From the tests performed, we observed that, with the hairpin technology, turn-to-turn is the weakest link in the insulation system. All the insulation models were partial discharge (PD) free from the beginning of the tests to breakdown and the root cause for breakdown was, in all cases, traced back to cracks on the surface of the insulation. This suggests that, depending on insulating enamel thickness and conductor geometry, some insulation systems are intrinsically PD free by design, despite the effect of aging. Considering the severe vibration profiles typical of EVs, and the principal breakdown mechanism (cracking of the insulation), mechanical stress coupled with thermal stress appears as the main aging driver. Therefore, this paper spotlights the lack of proper standards for the qualification of automotive electric motors and hints at the possibility that IEC 60034-18-41 considers dealing with motors that might be intrinsically partial discharge free even after long-term exposure to operational stresses.